Maksimisasi Keuntungan pada Usaha Hidroponik - Tsalis Kurniawan Husain; Farizah Dhaifina Amran (Jurnal Ilmiah Membangun Desa dan Pertanian, 2024)
Cultivating vegetables using the hydroponic method is essential in developing Indonesia's agricultural sector. Vegetables are a type of food that is consumed at any time, so there is always a stable demand all the time. The ever-increasing demand and awareness of the importance of nutritious food make hydroponics an attractive option. The potential for high demand for vegetables opens up many business opportunities to meet people's needs, including cultivating hydroponic vegetables. This research aims to analyze the actual profits of hydroponic businesses and the maximum profits they can generate. The research location is in Deedad Hidroponik, Tamalate District, Makassar City, from July to October 2023. Primary data was collected through interviews and direct observation of owners and employees, and secondary data was obtained from previous studies related to this research. Linear programming analysis via the Simplex Method is used to analyze Deedad Hidroponik's profit maximization. Profit analysis involves production costs, inputs, production results, and business revenues. The research results show that Deedad Hidroponikis can generate profits of IDR 6,980,492 from various types of vegetables. Deedad Hidroponik's source of profit comes from the production of 4 kinds of vegetables: lettuce, bok choy, kale, and spinach. Through a linear programming approach, Deedad Hidroponikwill achieve maximum profits if they plant vegetables with a combination of 625 planting holes for lettuce, 302 planting holes for bok choy, 257 planting holes for kale, and 260 planting holes for spinach; therefore, they could increase profits to IDR 7,496,783 with the potential increase of 7.38%. This shows that selecting vegetable types and resource allocation can be optimized to achieve maximum profits.